Relationship between speech analysis and Symantec-computational linguistics study - Ahmed Mahmoud, Ahmed Ragheb (s.n, 2012)
The research highlight the interactive relationship between speech and Symantec according to the output of computational linguistics, trying to monitor the relations of statistical research between context of phonology and meaningful result of that speech